Multimedia as an innovation in Pancasila Education learning: Perceptions of junior high school students - Pandu Rudy Widyatama (Pelita International Publishing, 2025)
This research is motivated by the still dominant lecture method in learning Pancasila Education at the junior high school level, which causes low student involvement. As technology develops, multimedia can be a solution to increase the effectiveness of learning. This study aims to explore students' perception of the use of multimedia in learning Pancasila Education at SMPN 16 Surabaya. The method used is qualitative research with a descriptive approach. The sample consisted of 20 students in class 8B who were selected using convenience sampling. Data was collected through observation, interviews, and documentation. The results of the study show that the use of PowerPoint, learning videos, regional song videos, and digital and printed LKPD increases student engagement and understanding. The Cognitive Theory of Multimedia Learning supports these findings, which suggests that the combination of visual and audio elements can improve students' comprehension. However, internet access constraints in the digital LKPD are still a challenge. In conclusion, multimedia increases the effectiveness of Pancasila Education learning. However, it is necessary to improve infrastructure and teacher training so that the use of multimedia is more optimal and inclusive for students.